Suppressed frictional noise on micro-triangle textured NBR inspired by ventral snake scales - Weibin Wu; Zeyun Li; Xue Yang; Qinqin Wang (Polymer Testing)
Nitrile butadiene rubber (NBR) is a basic ingredient of water-lubricated bearing which frequently suffers from abnormal frictional noise under certain shipping conditions. In this paper, we report a noise suppression approach of embedding micro-triangle arrays onto NBR surface by imitating the micro-fibril structures on ventral snake scales. The in-situ friction, vibration and noise experiments demonstrate that textured NBR could effectively inhibit stick-slip friction and eliminate frictional noise originated on flat surface regardless of load and sliding speed variation within the investigated range. Microscopic topography as well as indentation and tribological characteristics of textured and flat NBR were analyzed and compared to disclose the noise suppression mechanism. Micro-triangle texture reduces the spatial frequency of surface asperities and converts the skewness of asperity height distribution from negative to positive. Periodical reduced modulus and lower adhesion force were observed on textured NBR compared to flat reference. Simultaneous topography and friction measurements at microscale by atomic force microscopy (AFM) reveal periodical frictional peak at triangle edge on textured NBR. The friction on flat surface, however, is randomly mutated depending on the microscopic defects on topography. All above characteristics indicate unique superiority of interrupting stick-slip behavior and suppressing frictional noise by micro-triangle textures. This work provides a universal routine for attenuating frictional noise on NBR and validates its suppression mechanism by multi-scale analysis. The outcome is of great significance for developing low noise water-lubricated bearings and enhancing the mute level of ships.